A systematic review on the physical, physiological, perceptual, and technical-tactical demands of official 3 × 3 basketball games - Sansone, P.; Conte, D.; Tessitore, A.; Rampinini, E.; Ferioli, D. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To systematically review the physical, physiological, perceptual, and technical-tactical demands of official 3 × 3 basketball games. Methods: The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were followed. Three electronic databases (PubMed, Scopus, and Web of Science) were systematically searched to identify studies assessing physical, physiological, perceptual, and technical-tactical demands of 3 × 3 games. Data were also coded according to player sex and tournament phase. Quality assessment of the included studies was performed using a modified Downs and Black checklist. Results: Thirteen articles were finally included, with a mean quality of 8.6 (1.1) out of 11. Three-by-three basketball games have an intermittent profile (1:1 work-rest ratio), with a duration of ~15 minutes, and are characterized by short (6-8 s) ball possessions and considerable physical (17-33 accelerations, 24-44 decelerations, 62-94 changes of directions, and 17-24 jumps per game) and physiological (lactate: ~6.2 mmol·L-1) demands. Overall, the game performance profile is similar in males and females, with minor changes happening across tournament phases. Several key technical-tactical indicators were identified as discriminating winning and losing teams, such as better shooting and defensive efficiency, low number of turnovers, and implementing tactical actions involving more players, passing first, and ending possessions with shots from outside of the arch from the top of the key. Conclusions: Three-by-three basketball is an intermittent, physically demanding sport characterized by quick plays and specific tactical constraints. This review provides information that should be considered by performance staff to improve training prescription, game tactical plans, and for player selection and talent identification.